2016
DOI: 10.1002/eji.201546237
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to chromatin in intestinal macrophages link IL‐10 deficiency to inappropriate inflammatory responses

Abstract: Intestinal macrophages are uniquely programmed to tolerate exposure to bacteria without mounting potent inflammatory responses. The cytokine IL-10 maintains the macrophage anti-inflammatory response such that loss of IL-10 results in chronic intestinal inflammation. To investigate how IL-10-deficiency alters intestinal macrophage programming and bacterial tolerance, we studied changes in chromatin accessibility in response to bacteria in macrophages from two distinct niches, the intestine and bone-marrow, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 53 publications
(89 reference statements)
2
45
0
Order By: Relevance
“…However, consistent with previous findings, the IL-10 effect was most prominent in repression of LPS-induced inflammatory genes (Gopinathan et al, 2012;Lang et al, 2002a;Murray, 2005), possibly through epigenetic mechanisms Kobayashi et al, 2012;Simon et al, 2016). In addition, IL-10 also induced expression of LPS-repressed genes including those related to carbohydrate and lipid metabolism, in line with a recent report that the anti-inflammatory effects of IL-10 involve metabolic reprogramming of Mφs (Ip et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…However, consistent with previous findings, the IL-10 effect was most prominent in repression of LPS-induced inflammatory genes (Gopinathan et al, 2012;Lang et al, 2002a;Murray, 2005), possibly through epigenetic mechanisms Kobayashi et al, 2012;Simon et al, 2016). In addition, IL-10 also induced expression of LPS-repressed genes including those related to carbohydrate and lipid metabolism, in line with a recent report that the anti-inflammatory effects of IL-10 involve metabolic reprogramming of Mφs (Ip et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Chromatin profiling provides a mechanism as to why expression is changing, and whether observed changes may be transient or persistent. We have shown that chromatin accessibility can differentiate disease subtypes[10] and helps to describe genetic and environmental contributors to disease[11]. We therefore sought to determine whether multiple clinically distinct subclasses of adult CD exist by examining both gene expression, using RNA-seq, and chromatin accessibility, using Formaldehyde-Assisted Isolation of Regulatory Elements (FAIRE-seq)[12], in CD and non-IBD patient samples of unaffected colon mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The gene regulatory mechanisms controlling this behavior have been recently examined, revealing that the chromatin accessibility landscape of IL-10 knockout intestinal macrophages was similar to that of inflammatory macrophages. This finding suggests that IL-10-deficiency alone is sufficient to poise chromatin for an inflammatory response [35]. Overall, this extensive crosstalk between the microenvironment, LDTFs and SDTFs allows macrophages to control signal-specific transcriptional outputs that are important for their respective tissue of residency [6 ,7 ].…”
Section: The Temporal and Spatial Properties Of Macrophage Regulatorymentioning
confidence: 99%